Khabib Nurmagomedov: Manifestation of Public Diplomacy and Islamic Identity in UFC - Izulhaq, Mohammad Daffa; Nugraha, Raditya Abdurrahman; Aryowiloto, Julang (UIN Sunan Ampel Surabaya, 2022)
In contemporary times, public diplomacy is not necessarily facilitated by a state actor and the diplomatic process could still be interrelated with many sectors, including religion and sports. The Ultimate Fighting Championship (UFC) is one kind of public diplomacy arena in this context. In the UFC, there is a game of identity that is visible under certain conditions, for example, the one at the fighter Khabib Nurmagomedov, who is well known to have a very strong Islamic identity. This paper will dig into the manifestation of Islamic identity and public diplomacy in the UFC by Khabib Nurmagomedov from the beginning of his career in 2012 until his retirement. First of all, this paper describes the UFC as a public diplomacy arena, including the values it brings. Then proceed with the background of Khabib Nurmagomedov as a UFC fighter with his unique identity. After that, it will be explained how the symbolism of Islamic identity emerged and played in the UFC, with Khabib Nurmagomedov as the main focus. In the end, it can be concluded that Khabib Nurmagomedov has provided a unique position for Islamic identity in the UFC.